IMPLEMENTASI PERPUSTAKAAN SEKOLAH SEBAGAI SUMBER BELAJAR DALAM MENINGKATKAN PRESTASI BELAJAR SISWA - Mulyadi Sri Kamulyan; Febriana Primasari (Profesi Pendidikan Dasar, 2016)
The utilization existence of the library as a resource center for students in elementary school is a necessity that needs to be examined. Although the school does not have the personnel in charge of taking care of a special library, but it can be handled by a designated teacher under the control of the principal to optimize he library utilization. The effectiveness of implementation will have an impact on the growth of like reading in the school library for students on one hand also creativity of teachers in using library as a learning resource for certain theme, so that students want to come or use to the school library. There is a prediction that the utilization of school library is able to increase the student achievement.